Tunnel Hemodialysis Catheter Placement using the Supra-clavicular Approach to Overcome Stenosis of the Internal Jugular Vein At its Origin (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: supraclavicular vein cannulation; end-stage renal disease; tunnel dialysis access; arterial-venous fistula; pneumothorax; subclavian vein